Development and Validation of A HPTLC Method for the Estimation of Simvastatin and Ezetimibe. - Rathinaraj, Stephen (International Journal of Pharmaceutical & Biological Archive, 2010)
A simple, precise, accurate and rapid high-performance thin-layer chromatographic method has been developed and validated for the estimation of Simvastatin and ezetimibe simultaneously in combined dosage forms. The stationary phase used was precoated silica gel 60F 254. The mobile phase used was a mixture of chloroform: benzene: methanol: acetic acid (6.0:3.0:1.0:0.1 v/v/v/v). The detection of spots was carried out at 250 nm. The method was validated in terms of linearity, accuracy, precision and specificity. The calibration curve was found to be linear between 0.8 and 4.0 µg/spot for Simvastatin and 0.1 and 1.0 µg/spot for ezetimibe. The limit of detection and the limit of quantification for Simvastatin were found to be 170 ng/spot and 570 ng/spot respectively, and for ezetimibe, 20 ng/spot and 70 ng/spot respectively. The proposed method can be successfully used to determine the drug content of marketed formulation.